Impact of Diabetes Mellitus on Oral Health and Oral Health-Related Quality of Life in Older Adults in A Malaysian Healthcare Facility - Muntadar, Nur Aisyah; Kamarol Adlee, Nur Camelia Azlyn; Mohd Yusof, Eleena (UI Scholars Hub, 2024)
Objective: To investigate the association between oral health status and oral health-related quality of life (OHRQoL) in older adults with diabetes mellitus (DM). Methods: A cross-sectional study involving participants aged 60 and above from a Malaysian healthcare facility utilized structured interviews using the Geriatric Oral Health Assessment Index (GOHAI) questionnaire. Intraoral assessments, including BPE, DMFT index, evaluation of edentulism and assessment of restoration/denture type/quality, were conducted. Statistical analysis included independent sample t-test, one-way ANOVA, nonparametric, and correlation coefficient tests. Results: Among 69 participants (36 with DM, 33 without), with a mean age of 65.97 years, no significant differences in GOHAI scores were found between gender and diabetic status. However, distinctions concerning age were observed in GOHAI scores. Most participants reported poor OHRQoL, with a mean GOHAI score of 45.0 (±7.5). A notable difference was found in the pain and discomfort dimension of GOHAI between diabetic and non-diabetic participants. Conclusion: DM may affect specific dimensions of OHRQoL among older adults, highlighting the importance of comprehensive oral health assessments and tailored interventions. These findings contribute to understanding the diabetes-oral health relationship, informing strategies for improving oral health and quality of life among older adults with DM.